EVALUATING ONLINE AUTHENTIC READING ASSESSMENT - Ardiansyah, Hendro; Idris, Izazol; Imami, Muh. Khairul Wajedi (University of Muhammadiyah Malang, 2024)
The aim of the current research was to evaluate the online authentic reading assessment at the University of Muhammadiyah Malang, Indonesia. A total of 170 students who were participants in the assessment program participated in the current research. They were asked to rate and evaluate the assessment program based on five criteria: (1) planning; (2) teaching and learning; (3) student involvement; (4) coursework; and (5) course description aspects. This research employed quantitative approach. Descriptive analysis in Statistical Product and Service Solutions (SPSS) version 27 was used to analyse the data. The data were collected through an instrument adopted from the evaluation report for the instructors of the UMM. The instruments were valid and reliable to be used based on their content, face validity, and Cronbach alpha results. The results of the current research indicated that participants rated the program in a good category in all aspects of the criteria given, namely in the aspects of planning, teaching and learning, student involvement, coursework, and course description. Therefore, the online authentic reading assessment at the UMM was conducted sufficiently. The implications of the study suggest that future research should explore the integration of performance-based assessment with other approaches, such as competency-based assessment, situation-based assessment, or problem-based assessment.